Time series analysis of the subsidence of Esfarayen plain using radar interferometric method - mohammad motamedi rad; Reza Arjmandzadeh; Ebrahim Amiri; Farzad Amiri (تحقیقات کاربردی علوم جغرافیایی)
The persistent drought conditions and the increasing reliance on groundwater resources over the past decades have significantly expanded the areas affected by land subsidence across various regions of the country, leading to substantial damage. To mitigate the impacts of subsidence, a comprehensive and precise understanding of this phenomenon is essential. In recent decades, the Synthetic Aperture Radar (SAR) interferometric technique has emerged as a widely used method for measuring subsidence. This study utilizes field data, including piezometric wells, groundwater level fluctuations during minimum and maximum periods, and exploitation wells, to calculate aquifer discharge rates using Inverse Distance Weighting (IDW) interpolation. The aim is to analyze the time series of subsidence in the Esfarayen plain. Additionally, radar data from Sentinel-1 images were employed to estimate the subsidence rate during the first eight months of 2023. The findings reveal that subsidence in the study area ranged from 1 to 12 mm over the eight-month period, with 75.2% of the basin area classified as medium to highly critical. This indicates that the Esfarayen plain is in a critical state. The highest levels of water extraction and subsidence were observed in the southern regions of Sankhasat, Kharasha, Arg, Gazan, Jafarabad Kharaba, and Mehdiabad of Kal Beko wells, all of which fall within the highly critical zone. These areas require efficient groundwater management strategies to control and mitigate land subsidence.